Enhanced field emission characteristics of a 3D hierarchical Hfo2-Zno heteroarchitecture - Shisode, Raju T.; Suryawanshi, Sachin R.; Mistari, Chetan D.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Three dimensional (3D) HfO2-ZnO heteroarchitecture comprised of thin coating of HfO2 on self assembled 3D ZnO urchins with pointed apex has been synthesized using hydrothermal route followed by Pulsed Laser Deposition (PLD). The as-synthesized HfO2-ZnO heteroarchitecture was characterized using XRD, SEM, EDS, and (HR) TEM, in order to reveal its structural, morphological, and chemical properties. The HfO2-ZnO heteroarchitecture emitter exhibits superior field emission (FE) behaviour in contrast to the pristine ZnO urchins, demonstrated by delivery of high emission current density of similar to 885 mA/cm2 at an applied field of similar to 3.35 V/mm, against similar to 383 mA/cm(2) at an applied field of similar to 4.32 V/mu m for the pristine ZnO urchins emitter. Interestingly, the HfO2-ZnO heteroarchitecture emitter exhibits excellent emission current stability characterized with fewer fluctuations, owing to very good ion-bombardment resistance offered by the HfO2 coating. Furthermore, the heteroarchitecture thus obtained facilitates tailoring of the morphology with high aspect ratio and modulation of electronic properties as well, thereby enhancing the FE behaviour. Despite HfO2 being wide band gap and high-k material, the HfO2-ZnO heteroarchitecture exhibits potential as promising candidate for fabrication of high current density cold cathode
Keywords: 3D heteroarchitecture; Field Emission (FE); hydrothermal; PLD; TEM

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C